2010
DOI: 10.1097/tp.0b013e3181ce77e5
|View full text |Cite
|
Sign up to set email alerts
|

Return to Work and Social Participation: Does Type of Organ Transplantation Matter?

Abstract: Obtaining a paid or voluntary job posttransplantation is possible and should be strongly recommended by transplant professionals as a meaningful way to contribute to the society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
98
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 18 publications
16
98
1
2
Order By: Relevance
“…6 Employment rates after LTx fall short of employment rates in the general population and after other types of solid-organ transplantation. 4,7,8 This study confirms that LTx recipients are less likely to work than a comparable cohort of HTx recipients, and demonstrates that high local unemployment rates pose a further barrier to work participation among LTx recipients with no recent history of employment.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…6 Employment rates after LTx fall short of employment rates in the general population and after other types of solid-organ transplantation. 4,7,8 This study confirms that LTx recipients are less likely to work than a comparable cohort of HTx recipients, and demonstrates that high local unemployment rates pose a further barrier to work participation among LTx recipients with no recent history of employment.…”
Section: Discussionsupporting
confidence: 83%
“…[1][2][3] Although most transplant recipients are of working age and many desire to return to work, unemployment in this group is high and may be higher than among recipients of other solid organ transplants. [4][5][6][7] Returning to work has been associated with improved quality of life and clinical outcomes for solid organ transplant recipients. [6][7][8][9] Despite the benefits of returning to work, only a minority of LTx patients find work post-transplant.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study performed in Cambridge (England) included patients in follow-up of 30 years post-transplant, and demonstrated that receptors of female gender and aged over 60 years were important factors associated with reduced physical functioning of the SF-36 scale (17) . The marital status of participants was in line with findings of a study conducted in Belgium, in which most liver transplant patients were married, corresponding to 69.8% of the sample (18) . The patients' educational level was considered intermediate as 37.3% reported 10-12 years of study, and 40% less than ten years of study.…”
Section: Discussionsupporting
confidence: 62%